If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-2 + -1x) = 18 (-2 * 3 + -1x * 3) = 18 (-6 + -3x) = 18 Solving -6 + -3x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -3x = 18 + 6 Combine like terms: -6 + 6 = 0 0 + -3x = 18 + 6 -3x = 18 + 6 Combine like terms: 18 + 6 = 24 -3x = 24 Divide each side by '-3'. x = -8 Simplifying x = -8
| 7/8*6/5 | | 9m+24= | | 1/2w+7=2w-2 | | 27x-4=9x+2 | | x(x)-5+2forx=6 | | 2-4r=-14 | | 64x^3-49x=0 | | 2n=2n-1 | | 3t+2+2t=-53 | | x(x)-5+12= | | 5x^3+3x^2=125x+75 | | 8/11-2x=-2x+6/11 | | 5x^3/4+2=42 | | 29-5g+3=-3g+6g | | y+2=10 | | 32x-1/5=4 | | 3x-1/5=20 | | .2n-.594=3.5n+9.0 | | -.389y-.974=6.789y | | -3(2x-3)+15=9 | | 5(2x-6)=3(x+4) | | 15-(3m+7)=5+4m-18 | | 2x^2-10=20 | | 8y-6=7y+3 | | x/5+3=5 | | x/5-3=5 | | 6x+5x+15=180 | | 5x^2=24+2x^2 | | x=(1/2) | | 11/16n-3+1/4n=74 | | 12(y-2)=15y | | 8x^3-4x^2-60x=0 |